MENINGKATKAN KARAKTER PESERTA DIDIK MELALUI PENDIDIKAN AGAMA HINDU DI PASRAMAN: - - I Wayan Sugara Yasa (Jurnal Pendidikan Agama, 2023)
Abstract Education is a conscious effort made by a group of people to educate people from not knowing to knowing which is done by means of a learning process that enables students to actively develop a religious spirit of self-discipline, character, intelligence, noble character, and skills. Pasraman as a form of Hindu religious education has received legal legality in the implementation of Hindu religious education. The goal is that the implementation of religious education in the form of pasraman can be carried out properly according to the mandate of government regulations. Character is a natural attitude that exists in a person that distinguishes it from others. "Character is the quality, mental strength, morals, character or character of an individual which is a special personality, which is the driving force and driving force, and distinguishes it from other individuals. This study aims to describe the improvement of students' character through Hindu religious education at the Pasraman. This research is a qualitative research with data collection through observation, interviews, Focus Group Discussion (FGD) and literature studies. Data analysis used Ethnographic Content Analysis (ECA). Based on the results of data analysis, it was found that Pasraman is a Hindu educational institution that has been established since the Vedic era. In the past, pasraman were usually built in the middle of the forest so that teachers and students could concentrate on learning. During the kingdom era in the archipelago, Hindu education centers were known as the kadewaguruan mandala. While in Bali it is better known as padukuhan or pasraman. The pattern used in pasraman is spirituality and culture with an emphasis on building superior human character. This is closely related to the efforts of the Bali Regional Government in developing superior Balinese human resources. Hindu religious education requires a change in behavior as a whole, intact and integral which includes all aspects (potential) that exist in humans, both spiritual, emotional, skills and physical dimensions, because humans are the most important living beings among created beings. other god. Pasraman education with its unique educational pattern and curriculum should make a real contribution to efforts to improve the quality of national education and efforts to build national character. Hindus must always strive to improve the quality of education, both formal and informal education. Pasraman education can be an alternative model of superior education, which has its roots from the Vedic era to the kingdom era in the archipelago. The advantages of the pasraman education system in the past should be extracted and integrated with the competency needs of the modern era, so that the pasraman continues to find relevance.